The Role of Networks for Radical Change in Family Firms: A Systematic Literature Review - Reiners, Caroline; Kammerlander, Nadine (European Journal of Family Business, 2024)
In this literature review, we explore the pivotal role of family firms’ networks (e.g., relationships with employees, suppliers, or customers) in the detection and implementation of radical change. Prior research has mostly taken an isolated perspective, studying only one or two of the three fields “family firms,” “networks,” and “radical change.” We provide a comprehensive synthesis of existing literature, including 79 scholarly papers and use the Input-Process-Output (IPO) framework as an organizing instrument to analyze insights from research on family firms, networks, and radical change. We develop a research agenda targeted at linking networks, radical change detection, and radical change implementation in family firms, highlighting that family firm networks, with their distinct configurations and behaviors, can significantly influence the success or failure of radical change adaptation.